“Words to receive. Words to be received”: reflections on the Intercultural City museum work - Parrino, Lucia (Alterstice, 2015)
Although diversity has always been a fundamental characteristic of human societies, now more than ever it has become central to the political and research agenda. The question of how we can live together while enjoying our differences is a fundamental issue of our time, and the city is viewed as the most promising site to negotiate identities. That being so, what is the role of museums? How can local museums develop interventions that address local cultural diversity issues?In the first part of the article, I introduce the idea of “Intercultural City museum work.” I present a metadesign framework that aims to help museums emphasize the impact of diversity work on their local contexts, proposing the Intercultural City approach as a reference point. In the second part of the article, I describe the “Intercultural City museum work” and on using the metadesign framework with reference to MUST-Museo del Territorio Vimercatese, a civic museum on local history and identity in Vimercate, a town in the metropolitan area of Milan. Immigration to the geographical area over the past few decades and the resulting cultural diversity are neither reflected in the museum collections nor the permanent exhibitions. As a result, the museum decided to address these topics through services, events and special projects. In particular, I describe the exhibition Words to Receive. Words to be Received, designed and created by COI-Centro Orientamento Immigrati—a local immigrants’ resource centre—with the museum.